Assessing English Teaching Anxiety among English Tutors at Language Courses in Pare - Meta Nur Fitriyanti; Mirjam Anugerahwati; Sari Karmina (Universitas Cokroaminoto Palopo, 2026)
This study examines the level and factors of English teaching anxiety among English tutors in language courses in Pare, Kediri. Unlike most previous studies focusing on learners, this research explores tutors in non-formal educational settings, who often face emotional and linguistic challenges due to diverse academic backgrounds and varying student profiles. Using an adapted version of the Foreign Language Classroom Anxiety Scale (Horwitz et al., 1986) and the Foreign Language Teaching Anxiety Scale (Yoon, 2012), data were collected from 50 English tutors through an online questionnaire and analyzed descriptively. Results revealed that most tutors experienced low to moderate levels of anxiety, with the highest score found in the “Language Anxiety Overcome with Efforts” factor, suggesting active coping and emotional regulation. The findings indicate that teaching experience, contextual familiarity, and self-efficacy reduce anxiety and enhance professional confidence. Overall, teaching anxiety among non-formal tutors appears manageable and can function as a motivational force for reflective teaching and professional growth.